Application of soft computing in uncertainty analysis carried out within structural dynamics - Martowicz, Adam; Pieczara, Janina; Uhl, Tadeusz (Computer Assisted Methods in Engineering and Science, 2007)
The paper deals with the application of soft computing used in uncertainty analysis in the field of structural dynamics. Employing Genetic Algorithms, fuzzy sets theory as well as interval algebra authors show quite useful extension of well known approaches of solving eigenproblems considering assumed model uncertainties. During performed calculation, ranges of the first natural frequency of a simple FE model are found and then compared to those ones obtained with Monte Carlo simulation. As input uncertain parameters some of material properties are taken into account. The main objective of the work is to highlight possible advantages of the application in terms of reducing computation time meant for uncertainty analyses.